ИККИНЧИ ЖАҲОН УРУШИ ЙИЛЛАРИДА СУРХОНДАРЁ ВИЛОЯТИ АҲЛИНИНГ ФРОНТДА КЎРСАТГАН ҚАҲРАМОНЛИКЛАРИ - Тошов, К.Т. (SCIENCE and SOCIETY, 2020)
The author of the article examines the contribution of the Uzbek people to the Great Victory during World War II, the life, and courage of our compatriots, the heroism of the residents of Surkhandarya region at the front..
Keywords: front; catastrophe of fascism; military commissariat; writing; battle for life and death; defense; material wealth; war; heroism; friendship; partisans; mind; kindness; patriotism; courage